#TITLE_ALTERNATIVE# - RAFI RESPATI (NIM : 15111098), MUHAMMAD
Ocean currents are power energy potential sources in Indonesia that stores electrical energy potential up to 6000MW. The strongest tidal currents were recorded in Indonesia is in the Strait of Capalulu, Sula Archipelago, North Maluku. This study aims to map the power potential that comes from the ocean currents in the strait. There are 8 observation points placed along the Strait of Capalulu. Based on the results obtained point as a power potential locations currents that point 5 and 6. Point 5 has the potential of electricity for one month at 489.614 kWh in the west wind and 572.131 kWh in the eastern monsoon. While the point 6 has the potential electrical energy for one month at 428.529 and 526.896 kWh kWh in the eastern monsoon.